ALGUMAS NOÃ‡Ã•ES DE ESTATÃSTICA: SUA UTILIZAÃ‡ÃƒO NA EXPERIMENTAÃ‡ÃƒO AGRÃCOLA - Conagin, A. (REVISTA DE AGRICULTURA, 2016)
ALGUMAS NOÃ‡Ã•ES DE ESTATÃSTICA: SUA UTILIZAÃ‡ÃƒO NA EXPERIMENTAÃ‡ÃƒO AGRÃCOLA